Psoriasis in those planning a family, pregnant or breast‐feeding. The Australasian Psoriasis Collaboration. (23rd May 2017) - Rademaker, Marius; Agnew, Karen; Andrews, Megan; Armour, Katherine; Baker, Chris; Foley, Peter; Frew, John; Gebauer, Kurt; Gupta, Monisha; Kennedy, Debra; Marshman, Gillian; Sullivan, John
Abstract: The Australasian Psoriasis Collaboration has reviewed the evidence for managing moderate to severe psoriasis in those who are pregnant or are breast‐feeding, or planning a family. The severity of the psoriasis, associated comorbidities and specific anti‐psoriasis treatment, along with other exposures, can have a deleterious effect on pregnancy outcomes. Psoriasis itself increases the risk of preterm and low birthweight babies, along with spontaneous and induced abortions, but no specific birth defects have been otherwise demonstrated. The baseline risk for a live born baby to have a major birth defect is 3%, and significant neuro‐developmental problem is 5%. In Australia, pregnant women with psoriasis are more likely to be overweight or obese, depressed, or smoke in their first trimester, and are also less likely to take prenatal vitamins or supplements. Preconception counselling to improve maternal, pregnancy and baby health is therefore strongly encouraged. The topical and systemic therapies commonly used in psoriasis are each discussed separately, with regards to pregnancy exposure, breast‐feeding and effects on male fertility and mutagenicity. The systemic therapies included are acitretin, adalimumab, apremilast, certolizumab, ciclosporin, etanercept, infliximab, ixekizumab, methotrexate, NBUVB, prednisone, PUVA, secukinumab and ustekinumab. The topical therapies include dithranol (anthralin), calcipotriol, coal tar, corticosteroids (weak, potent and super‐potent), moisturisers, salicylic acid, tacrolimus, and tazarotene. As a general recommendation, effective drugs that have been widely used for years are preferable to newer alternatives with less foetal safety data. It is equally important to evaluate the risks of not treating, as severe untreated disease may negatively impact both mother and the foetus.